Cross-layer capacity optimisation in WiMAX orthogonal frequency division multiple access systems with multi-class quality of services and users queue status - Matalgah, Mustafa M; Hammouri, Omar M; Paudel, Bimal (IET communications, 2014)
Given the broad range of applications supported, high data rate required and low latency promised; dynamic radio resource management is becoming vital for the air interface technologies such as WiMAX and LTE adopted by international standards. This study considers the OFDMA system, which has been implemented in both WiMAX and LTE technologies as their air interface multiple access mechanism. A framework for optimised resource allocation with QoS support that aims to balance between service provider's revenue and subscriber's satisfaction is proposed in this study. A cross-layer optimisation design for subchannel and power allocations with the objective of maximising the capacity (in bits/symbol/Hz) subject to fairness parameters and QoS requirements as constraints is presented. The optimisation does not only consider users channel conditions but also queue status of each user as well as different QoS requirements. The QoS classes adopted by the IEEE 802.16e standard, for WiMAX technology, are utilised in this study. In the proposed framework, the problem of power allocation is solved analytically whereas the subchannel allocation is solved using integer programming exhaustive search. The simulation and numerical results obtained in this study have shown improved system performance as compared to other optimisation schemes known in the literature.